Towards best practices for residential carpentry safety: Multiple case study analysis. (February 2023) - Lucas, Jason; Bausman, Dennis; Magxaka, Marchell; Haidary, Tanin
Highlights: The safety practices for small residential carpentry firms were explored. Interview were utilized to develop case studies documenting company level safety practices. Trends of practices were aligned with safety performance in proposing best practices. Identified practices were also compared to literature about larger company safety practices to gauge disparity due to resources. Abstract: Introduction: Carpentry firms face some of the most dangerous working conditions in residential construction. Since these companies are often small, they may not have developed safety policies commonly found in larger companies. The research presented in this paper examines the industry's current practices and identifies ways to help improve their safety performance. Methods: A survey was conducted to benchmark practices used by carpenters in residential construction. Interviews were used to develop case studies documenting safety practices and policies. A cross-sectional analysis of the case studies allowed for identifying trends and differences based on company safety performance. Results: The results indicated that owner and upper-level management's direct involvement in safety training and hiring practices affect the company's overall safety performance. Additionally, when a company focuses on and checks worker competence, there are fewer issues related to safety and the benefit of improved quality. Further, the formality of policies and incorporating them into training indicates a better safety culture and improved safety performance. One area in the literature that affected worker safety performance is incentive programs; however, no company involved in the current study utilized incentives. Most expressed a negative view of incentive use. Conclusion: Some differences between companies with a better safety performance record by Experience Modifier Rate (EMR) and those with a poorer performance record are how the owner or senior-level management is involved in safety and hiring. Additionally, these companies manage risk differently by ensuring that workers are skilled correctly, or they will find someone else to do it, even if it means utilizing an independent contractor. Practical Applications: This study identified practices that owners could incorporate into company-level management to help improve safety performance. Ultimately, an improved safety culture will reduce the potential for accidents and injuries.